Rieche formylation of carbon nanotubes – one-step and versatile functionalization route. Issue 81 (6th November 2017) - Kolanowska, Anna; Kuziel, Anna; Li, Yuliu; Jurczyk, Sebastian; Boncel, Sławomir
Abstract : We present the direct and one-step Rieche formylation of carbon nanotubes (CNTs) as the most effective (4.00 mmol g −1 ) functionalization route via formylation. Abstract : We present the direct and one-step Rieche formylation of carbon nanotubes (CNTs) as the most effective (4.00 mmol g −1 ) functionalization route via formylation. Indeed, classical methods, i.e. three-step protocols based on CNT oxidation–reduction–partial oxidation (COOH ≫ CH2 OH ≫ CHO), were revealed as less effective and more troublesome. All CNT-CHO products were comprehensively analysed by cross-verified potentiometric titration, scanning electron microscopy (SEM), thermogravimetry (TGA), Fourier transform infrared spectroscopy (FT-IR) and Raman spectroscopy.